Preparation and characterization of polycarbonate/multiwalled carbon nanotube nanocomposites - Larosa, Claudio; Patra, Niranjan; Salerno, Marco; Mikac, Lara; Merijs Meri, Remo; Ivanda, Mile (Beilstein Journal of Nanotechnology, 2017)
A polymer nanocomposite was produced by ultrasonic-assisted dispersion of multiwalled carbon nanotubes (MWCNTs) in a polycarbonate matrix using p-xylene and dichloromethane as the solvents. The filler loading was varied from 1 to 3 wt % in order to examine the effect of MWCNTs on the structure and properties of the composites. The nanocomposites were characterized by DSC, DTA, TGA, UV–vis, FTIR and Raman spectroscopy to evaluate the changes induced by the filler in the polymer matrix. UV–vis, FTIR and Raman spectroscopy measurements confirmed the presence of the dispersed phase in the composite films, while TGA and DSC analysis of the nanocomposites revealed enhanced thermal stability and decreased crystallinity, respectively, as compared to the neat polymer. The proposed composites can find application in a number of everyday products where polycarbonate is the base polymer.
Keywords: multiwalled carbon nanotubes; nanocomposites; polycarbonate; thermal analysis; vibrational spectroscopy

Ullmann’s Encyclopedia of Industrial Chemistry - Serini, V. (Polycarbonates, 2012)

Crystallization behavior of Bisphenol-A polycarbonate: effects of time, temperature, and molar mass - Seungman, S. (Virginia Polytechnic Institute and State University, 2000)

Polymer Crystallization: Obervations, Concepts and Interpretations - Reiter, G.; Sommer, J.-U. (Springer, 2008)

(untitled) - Miladinova, P. M.; Konstantinova, T. N. (J. Chem. Technol. Metall., 2015)

Perspectives of Fullerene Nanotechnology - Loutfy, R. O.; Withers, J. C.; Abdelkader, M.; Sennett, M. (Carbon Nanotube–Polycarbonate Composties, 2002)

(untitled) - Larosa, C.; Stura, E.; Eggenhöffner, R.; Nicolini, C. (Materials, 2009)

(untitled) - Che, B.; Nguyen, B.; Nguyen, L.-T. T.; Nguyen, H.; Nguyen, V.; Van Le, T.; Nguyen, N. (Chem. Cent. J., 2015)

(untitled) - Chen, L.; Pang, X.-J.; Yu, Z.-L. (Mater. Sci. Eng., A, 2007)

(untitled) - Jindal, P.; Yadav, R. N.; Kumar, N. (Iran. Polym. J., 2017)

MultiComp - COST Action CA15107

(untitled) - Mishra, N.; Patra, N.; Pandey, S.; Salerno, M.; Sharon, M.; Sharon, M. (J. Therm. Anal. Calorim., 2014)

(untitled) - Patra, N.; Hladik, J.; Martinová, L. (J. Therm. Anal. Calorim., 2014)

(untitled) - Patra, N.; Salerno, M.; Cozzoli, P. D.; Athanassiou, A. (J. Colloid Interface Sci., 2013)

(untitled) - Patra, N.; Salerno, M.; Cozzoli, P. D.; Barone, A. C.; Ceseracciu, L.; Pignatelli, F.; Carzino, R.; Marini, L.; Athanassiou, A. (Composites, Part B, 2012)

(untitled) - Hamada, N.; Sawada, S.-i.; Oshiyama, A. (Phys. Rev. Lett., 1992)

(untitled) - Kataura, H.; Kumazawa, Y.; Maniwa, Y.; Umezu, I.; Suzuki, S.; Ohtsuka, Y.; Achiba, Y. (Synth. Met., 1999)

(untitled) - Lauret, J.-S.; Voisin, C.; Cassabois, G.; Delalande, C.; Roussignol, P.; Jost, O.; Capes, L. (Phys. Rev. Lett., 2003)

(untitled) - Thorat, S.; Patra, N.; Ruffilli, R.; Diaspro, A.; Salerno, M. (Dent. Mater. J., 2012)

(untitled) - Patra, N.; Barone, A. C.; Salerno, M. (Adv. Polym. Technol., 2011)

(untitled) - Patra, N.; Jayaseelan, D. D.; Lee, W. E. (J. Am. Ceram. Soc., 2015)

Handbook of Fourier Transform Raman and Infrared Spectra of Polymers - Kuptsov, A. H.; Zhizhin, G. N. (Elsevier, 1998)

(untitled) - Bokobza, L.; Zhang, J. (eXPRESS Polym. Lett., 2012)

(untitled) - Babal, A. S.; Gupta, R.; Singh, B. P.; Singh, V. N.; Dhakate, S. R.; Mathur, R. B. (RSC Adv., 2014)